The Currency of Fantasy: Discourses of Popular Culture in International Relations - Wang, Ningchuan (International Studies. Interdisciplinary Political and Cultural Journal, 2013)
The “facts” of international politics constitute the first-order representations of political life and can be reflected in popular entertainment as second-order or fictional representations. This article demonstrates that discourses of popular culture are powerful and implicated in International Relations (IR) studies. The article makes two correlated claims: the first is that the humanist and anthropological methodology often used to analyse pop culture could also be used to analyse international issues, if appropriately contextualized; the second claim is that a nation can manifest its ‘discourse’ in international politics via its popular culture, as soft power.